High Aspect Ratio Polymeric Nanoneedle Arrays. Issue 4 (5th March 2021) - McCormack, James C.; Podhorska, Lucia; Delaney, Colm; Zhang, Fengyuan; Rodriguez, Brian J.; Kelleher, Susan M.
Abstract: High aspect ratio (HAR) nanoneedle arrays can be used to tune the intrinsic properties of substrates such as their wettability and reflectivity. Here, a simple and scalable fabrication method for producing dense arrays of freestanding polyethylene glycol (PEG) nanoneedles with sub 50 nm tips and surface coverage up to 83 needles per µm 2 is presented. Two distinct sets of silicon nanoneedle master arrays with base diameters between 15 and 265 nm and heights between 146 and 613 nm are fabricated using block copolymer micelle lithography. Replication of selected silicon masters using photocurable polymers produces HAR PEG nanoneedle arrays with feature base diameters ranging between 15 and 292 nm and heights between 133 and 656 nm. At their maximum, the aspect ratio of the pillars is 4.6. PEG nanoneedle arrays are produced using polymers with two different molecular weights as well as two different photoinitiators, showing the versatility of the process. Abstract : A versatile and accessible approach enabling patterning of Si and polyethylene glycol nanoneedle arrays across centimetre‐scale surface areas is discussed. Block copolymer micelle lithography is applied as a straightforward method for Si nanoneedle master array fabrication while replica molding using photocurable acrylate‐terminated polymers is explored as a direct means of translating these structures onto soft biocompatible materials.